HYBRID VIGOUR IN BRINJAL (SOLANUM MELONGENA L.) - S. B. DESHMUKH,; G. W. NARKHEDE,,; L. K. GABALE,; V. N. DOD, (The Bioscan, 2015)
The present investigation was undertaken in brinjal to estimate the magnitude of heterosis of some economically important traits. 36 F1 hybrids generated by half diallel crosses of nine pure diverse parent and these F1s along with 9 parents and 2 checks were evaluated in a randomized block design with three replication at Research farm of Department of Horticulture. The results showed considerable heterobeltiosis for traits viz. fruit diameter 60.73 % (Local C-1 x GADB-1), fruit weight 136.67 % (Asond Long x GADB-1), yield/plant 83.33 % (Local-3 x Local-2) and days to 50% flower -24.72% (Asond Long x GADB-1); moderate estimate for infestation of shoot and fruit borer -40.33 % (Asond Long x Selection-167) and chlorophyll content. Crosses displaying significant heterobeltiosis for yield also possessed marked heterotic advantage in one or more component characters emphasizing their role in increasing yield. The present study reveals good scope for isolation of pure lines from the progenies of heterotic F1s as well as commercial exploitation of heterosis in brinjal.